The Role of Business Processes and Enterprise Architectures in the Development of Organizational Self-Awareness - Magalhães,M. Rodrigo (2008)
This paper is about a partnership between two disciplines: organizational studies and information systems engineering. It is argued that organizational studies has much to benefit from the conceptual development that has been taking place in the representation of organizational processes and enterprise architectures (EA) and that systems engineering can greatly expand its execution capability by absorbing a variety of messages coming from social or organizational theory. The concept of Organizational Self-Awareness (OSA) is offered as the contextual framework for the discussion. OSA is a process which involves, firstly, the efforts of the individual organizational member in getting to know his/her work environment, through sensemaking. Sensemaking is influenced by a number of factors, some related to the individuals psychological makeup, others related to the individuals work environment. EAs can play a relevant role in sensemaking. From activity theory the paper highlights the process of consciousness formation in human beings as well as the mediating artefacts that shape and constrain the acquisition, accumulation and development of knowledge and self-knowledge. Among the many mediating artefacts in the work environment EAs are a special type. EAs are also boundary objects due to their distinctive ability to influence perspective making and perspective taking in the process of organizational sensemaking. The paper concludes that the design and use of EAs can play a crucial role in the formation of a collective mind about the state of the organizational processes and therefore about the state of the organization.